The impact of stopping high-energy oral nutritional supplements on eating behaviour and weight gain. Issue 11 (25th March 2015) - Wright, Charlotte M; Chillingworth, Anna
Abstract : Background and aims: Many children referred to a tertiary feeding clinic are already taking high-energy oral nutritional supplements (HEOS), but these often seem not clinically useful. We undertook a retrospective review of all children on HEOS at the time of referral to the clinic in order to describe their subsequent progress in terms of growth and feeding behaviour. Results: A total of 48 children were on HEOS at referral and withdrawal of HEOS was attempted in 38 children, aged median 3.0 years (range 0.7–10 years) who were taking volumes equivalent to 2/3 of total daily energy requirements. The children tended to be very short and slim (median height SD score (SDS) −2.0 (range −5.7 to 1.9); body mass index −2.0 (−5.1 to 1.9)). Half had normal neurodevelopment (ND) but 4 (11%) had learning disability and 4 (11%) severe ND problems. By last follow-up after 0.86 (0–2.9) years, 30 (79%) had stopped all feeds. Those who stopped had a mean (SD) change in weight of 0.08 (0.6) SDS (range −0.88 to +1.59). Five children (17%) showed significant catch-up weight gain after stopping feeds, of whom three had been referred for weight faltering and possible tube feeding. Improvement in feeding behaviour was documented in 76% (29). Conclusions: The use of HEOS in children suppresses appetite for solid food due to energy compensation. In some cases, HEOS may perpetuate or even cause weight faltering. It should not be assumed that failure to respond to HEOS is an indication for tube feeding.